Management of postpartum reproduction in crossbred cows with Dinoprost - SINHA, V K; SINGH, BALRAJ; SINHA, A K (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 32 cows belonging to different small private farms around Ranchi. 'Dinoprost'25 mg was administered intramuscularly to each of 20 cows within 6 hrs of parturition and 12 cows were kept ascontrol. The incidence of retention offetal membranes in 'Dinoprost' treated cows was significantly (P
Keywords: Postpartum; crossbred cows; Dinoprost; involution of uterus; retention of fetal membranes